The art of public speaking - Carnegie, Dale, 1888-1955; Esenwein, J. Berg (Joseph Berg), 1867-1946 (Mineola Ixia press, 2017)
"A pioneer in the field of self-help, Dale Carnegie distilled his experiences as a salesman and lecturer in his first guide to successful speech-making, The Art of Public Speaking. This predecessor to his bestseller, How to Win Friends and Influence People, was co-written with J. B. Esenwein. Its direct, practical advice for emphasizing ideas for easy comprehension and high impact ranges from finding an appropriate rhythm to conquering stage fright. Avoiding the use of tricks and shortcuts, the authors suggest methods for developing one's thoughts in order to form an original, authentic manner of speaking. They advise speakers to practice their presentation skills, offering useful tips for speech-making in both personal and professional situations. First published in 1915, this classic continues to encourage people from all walks of life to overcome their self-consciousness and increase their effectiveness and comfort as public speakers"--
Includes index.
Keywords: Public speaking; Oratory; SELF-HELP / Motivational & Inspirational; SELF-HELP / Personal Growth / General